Transcriptome and Proteome Analysis Identified Genes/Proteins Involved in the Regulation of Leaf Color in Paulownia fortunei - Hu Li; Weili Tian; Yongming Fan (Horticulturae)
Paulownia fortunei are economically important trees in China. A greening mutant was used to study greening by comparative transcriptomics and proteomics using leaf tissues from wild-type and greening mutant growing under normal conditions. Chlorophyll content analysis showed a decrease in the chlorophyll b content in the mutant line. Non-parametric transcriptome and proteome analyses were performed to screen for genes and proteins active in the regulation of P. fortunei greening. qRT-PCR was carried out to confirm 10 genes identified in the transcriptome. In the transcriptome analysis, the pathways associated with the yellow phenotype included tRNA amino acid biosynthesis, nitrogen metabolism and circadian rhythm as represented by the genes encoding Vals, gltx, aspS, NR, GluL, gdhA, phyB, CSNK2A and CSNK2B. The iTRAQ-based proteomics analysis indicated that photosynthesis and carotenoid biosynthesis were altered in the chlorophyll-deficient P. fortunei and petH, petF, atpF and Z-ISO were the key proteins dysregulated in the greening mutants compared to the wild-type. Together, the transcriptomic and iTRAQ analyses identified 10 DEGs that were perturbed in the greening mutants in the main pathways of photosynthesis, starch and sucrose metabolism, glutathione metabolism and peroxisome functions. PetJ, E3.2.1.21, GST and CAT were differentially regulated in the chlorophyll-deficient mutant.